2003
DOI: 10.1093/aje/kwf187
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Stress Disorder and Chronic Fatigue Syndrome-like Illness among Gulf War Veterans: A Population-based Survey of 30,000 Veterans

Abstract: The authors estimated the prevalence of post-traumatic stress disorder (PTSD) and illness resembling chronic fatigue syndrome (CFS) in the entire population of Gulf War and non-Gulf-War veterans. They also evaluated the relation between the extent of deployment-related stress and the risk of either PTSD or CFS. In 1995-1997, the authors conducted a health survey in which these two symptom-based medical diagnoses in a population-based sample of 15,000 Gulf War veterans representing four military branches and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
267
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(282 citation statements)
references
References 25 publications
13
267
0
2
Order By: Relevance
“…Epidemiological research increasingly suggests that exposure to traumatic events is related to adverse health outcomes and the onset of specific diseases. 3,4,59 To gain more insight in human adaptation to traumatic stress and the relation of these processes with alterations in GR expression, glucocorticoidimmune interaction and psychopathology, further research in a longitudinal, instead of a cross-sectional design, is preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological research increasingly suggests that exposure to traumatic events is related to adverse health outcomes and the onset of specific diseases. 3,4,59 To gain more insight in human adaptation to traumatic stress and the relation of these processes with alterations in GR expression, glucocorticoidimmune interaction and psychopathology, further research in a longitudinal, instead of a cross-sectional design, is preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of individual diagnoses within the broad diagnostic categories of hospitalizations significantly associated with response focused on the five most frequent three-digit diagnostic codes to examine their association with response. Additionally, specific ICD-9-CM diagnoses that have previously been indicative of chronic multisymptom illness were explored [14][15][16][17][18][19][20][21][22][23][24][25]. To further evaluate health care usage differences between responders and nonresponders, the mean number of days spent hospitalized or in outpatient care during the year prior to enrollment was also compared.…”
Section: Health Care Datamentioning
confidence: 99%
“…Research conducted after other military conflicts has shown that deployment stressors and exposure to combat result in considerable risks of mental health problems, including post-traumatic stress disorder (PTSD), major depression, substance abuse, impairment in social functioning and in the ability to work, and the increased use of health care services. [1][2][3][4][5][6][7][8] One study that was conducted just before the military operations in Iraq and Afghanistan began found that at least 6 percent of all U.S. military service members on active duty receive treatment for a mental disorder each year. 9 Given the ongoing military operations in Iraq and Afghanistan, mental disorders are likely to remain an important health care concern among those serving there.…”
mentioning
confidence: 99%